New Auxiliary Vector Synthesis for Expanding Linear Modulation Range With the Ability to Eliminate CMV Spikes in the SVM Three-Phase Inverters - Jin Huang; Kaicheng Li (IEEE Access)
Some strategies are used to reduce the high output common-mode voltage (CMV) in three-phase inverters with the space-vector modulation (SVM). However, these reduced CMV (RCMV) strategies may still lead to high spikes in some cases. The traditional auxiliary vectors are used to eliminate the CMV spikes in some RCMV strategies, which have the lower total harmonic distortion (THD) in RCMV SVMs. This paper proposes a new auxiliary vector synthesis SVM (NAVSSVM) strategy. In the NAVSSVM, the new auxiliary vectors are a set of vectors with variable angles. Compared to the use of traditional auxiliary vectors, the new auxiliary vector synthesis expands the linear modulation range of the inverter to the maximum when the modulation index $M_{a}~\gt 1$ . Through optimization, the optimal NAVSSVM is found to expand the modulation region without the CMV spikes in the low $M_{a}$ . In addition, the NAVSSVM strategy maintains the low THD characteristic of the auxiliary vector synthesis method. The feasibility and effectiveness of the NAVSSVM are verified by the simulations and experiments in a three-phase inverter.